A [3]Rotaxane Host Selects Between Stereoisomers. Issue 17 (24th March 2018) - Denis, Mathieu; Goldup, Stephen Michael
Abstract : What has it got in its pockets? A new approach to the selective binding and reporting of stereoisomers using mechanical bonding to produce a well‐defined three‐dimensional binding pocket was recently reported by Beer and co‐workers. The highly stereoselective binding of stereoisomers by the reported [3]rotaxane suggest that the use of the mechanical bond to engineer a binding pocket has great potential for the development of stereoselective hosts.